Waterproofing Admixture and Aloe Vera Biopolymer Gel in Concrete: Microstructure, Durability and Structural Validation - Marlon Cubas; Pedro Patazca; Robert Suclupe; Luis Villegas; Omar Coronado; Oscar Alvarado; Javier Guerrero; Brayan Perleche (Civil Engineering Journal, 2026)
Concrete durability in aggressive environments is often limited by chloride ingress, carbonation, and sulfate attack, which compromise structural integrity and increase maintenance costs. This study examines the combined effects of an integral waterproofing admixture (Sika®-1, 3– 4% cement weight) and Aloe vera biopolymer (1–2% cement weight) on mechanical performance, durability, and microstructural characteristics of conventional concrete. Four mixtures were produced: a control (P1) and three hybrid formulations (P2: 4%S1+1%AV; P3: 3.5%S1+1.5%AV; P4: 3%S1+2%AV), subjected to fresh state testing, strength development at 7, 14, and 28 days, and durability assessment including water permeability, chloride penetration, sulfate resistance, carbonation depth, ultrasonic pulse velocity, and surface abrasion through 56 days, alongside X-ray diffraction, Fourier-transform infrared spectroscopy, and scanning electron microscopy analysis. The optimal mixture (P4) achieved 28.77 MPa compressive strength, reduced water permeability to 0.00420 cm/s, lowered chloride penetration to 138.38 Coulombs, and minimized carbonation depth to 0.44 mm, with microstructural analysis revealing enhanced C-S-H gel densification and refined porosity. Pilot-scale reinforced concrete frames fabricated with P4 exhibited 9.6% lower maximum strain, confirming improved structural stiffness and durability. Techno-economic evaluation yielded an index of 1.104, demonstrating economic viability despite an 11.2% material cost increase. These results support the use of the hybrid admixture system as a sustainable option for extending concrete service life in marine, industrial, and tropical environments.